2007
DOI: 10.1149/1.2756294
|View full text |Cite
|
Sign up to set email alerts
|

The Instability of a-Si:H TFT under Mechanical Strain with High Frequency ac Bias Stress

Abstract: The instability of amorphous Si thin film transistors under uniaxial strain has been studied. Compared to the effect of tensile bias stress, larger threshold voltage shift is observed under compressive bias stress. These results are related to the damage of weak Si-Si bonds during the ac bias stress. However, the V th shift of devices on the re-flattened substrate is larger after tensile strain than that of compressive strain. In addition, the defeat diminished effect of tensile situation is decreased after re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…2͑b͒. 10 The energy barrier height under the compressive stress is the lowest than those on the states of the flat and the tensile. A reduced E a can contribute the enhanced hole mobility to the p-channel poly-Si TFT.…”
mentioning
confidence: 99%
“…2͑b͒. 10 The energy barrier height under the compressive stress is the lowest than those on the states of the flat and the tensile. A reduced E a can contribute the enhanced hole mobility to the p-channel poly-Si TFT.…”
mentioning
confidence: 99%
“…The threshold voltage of MO TFTs will shift to positive or negative when it is used in the foldable displays [4,5]. A positive shift would not affect the output of the SCAN signal.…”
Section: The Proposed Scan Drivermentioning
confidence: 99%
“…In foldable displays, metal oxide (MO) TFTs are suitable to be used for high mobility and a low fabrication temperature [3]. Previous research has shown that compressive strain and tensile strain have different effects on the characteristics of MO TFTs [4,5], which will cause the circuits such as the pixel circuit and scan driver circuit in the display panel to not work properly.…”
Section: Introductionmentioning
confidence: 99%